Mental performance in 8-year-old children fed reduced protein content formula during the 1st year of life: safety analysis of a randomised clinical trial. (22nd January 2016) - Escribano, J.; Luque, V.; Canals-Sans, J.; Ferré, N.; Koletzko, B.; Grote, V.; Weber, M.; Gruszfeld, D.; Szott, K.; Verduci, E.; Riva, E.; Brasselle, G.; et al.
Abstract: In humans, maximum brain development occurs between the third trimester of gestation and 2 years of life. Nutrition during these critical windows of rapid brain development might be essential for later cognitive functioning and behaviour. In the last few years, trends on protein recommendations during infancy and childhood have tended to be lower than that in the past. It remains to be demonstrated that lower protein intakes among healthy infants, a part of being able to reduce obesity risk, is safe in terms of mental performance achievement. Secondary analyses of the EU CHOP, a clinical trial in which infants from five European countries were randomised to be fed a higher or a lower protein content formula during the 1st year of life. Children were assessed at the age of 8 years with a neuropsychological battery of tests that included assessments of memory (visual and verbal), attention (visual, selective, focused and sustained), visual-perceptual integration, processing speed, visual-motor coordination, verbal fluency and comprehension, impulsivity/inhibition, flexibility/shifting, working memory, reasoning, visual-spatial skills and decision making. Internalising, externalising and total behaviour problems were assessed using the Child Behaviour Checklist 4–18. Adjusted analyses considering factors that could influence neurodevelopment, such as parental education level, maternal smoking, child's gestational age at birth and head circumference, showed no differences between feeding groups in any of the assessed neuropsychological domains and behaviour. In summary, herewith we report on the safety of lower protein content in infant formulae (closer to the content of human milk) according to long-term mental performance.